Complement receptor 3 mediates ruffle-like, actin-rich aggregates during phagocytosis of Leishmania infantum metacyclics - Dixit, Upasna Gaur (Exp Parasitol, 2020)
The parasitic protozoan Leishmania infantum resides primarily in macrophages throughout mammalian infection. Infection is initiated by deposition of the metacyclic promastigote into the dermis of a mammalian host by the sand fly vector. Promastigotes enter macrophages by ligating surface receptors such as complement receptor 3 (CR3), inducing phagocytosis of the parasite. At the binding site of metacyclic promastigotes, we observed large asymmetrical aggregates of macrophage membrane with underlying actin, resembling membrane ruffles. Actin accumulation was observed at the point of initial contact, before phagosome formation and accumulation of peri-phagosomal actin. Ruffle-like structures did not form during phagocytosis of attenuated promastigotes or during phagocytosis of the intracellular amastigote form of L. infantum. Entry of promastigotes through massive actin accumulation was associated with subsequent delay in fusion of the parasitophorous vacuole (PV) with the lysosomal markers LAMP-1 and Cathepsin D. Actin accumulation was also associated with entry through CR3, since macrophages from CD11b knockout (KO) mice did not form massive aggregates of actin during phagocytosis of metacyclic promastigotes. Furthermore, intracellular survival of L. infantum was significantly decreased in CD11b KO compared to wild type macrophages, although entry rates were similar. We conclude that both promastigote virulence and host cell CR3 are needed for the formation of ruffle-like membrane structures at the site of metacyclic promastigote phagocytosis, and that formation of actin-rich aggregates during entry correlates with the intracellular survival of virulent promastigotes.